The application of knowledge management processes in secondary schools and their relation to the performance of their teachers from the point of view of the teachers (Latakia University Journal - Arts and Humanities Sciences Series, 2018)
This research aims to identify the application of knowledge management processes in secondary schools and their relation to the performance of their teachers from the point of view of the teachers in Lattakia city, and to identify the effect these variables (kind, the scientific qualification and educational, the experience, age) on the application of knowledge management processes and teachers performance. The present research used the descriptive analytical approach, and to achieve the objectives of the research, questionnaire has been consisted of (37) statements for the application of knowledge management processes, and a questionnaire consisted of (26) statements for performance of their teachers, were applied on sample (378) Teaching Staff Members during the academic year of (2016 - 2017). The present research used the descriptive analytical approach, Validity of the questionnaire was established though a jury of (9) of the teaching staff of educational at Tishreen University. The research results showed that the degree of application of knowledge management processes in secondary schools and the performance of their teachers were middle rated from the point of view of the teachers, also results showed there is a positive correlation between application of knowledge management processes in secondary schools and the performance of their teachers, and is a positive effect to interaction between these variables (kind, the scientific qualification and educational, the experience, age) and application of knowledge management processes and teachers performance. The research suggested given more important for knowledge management in the schools, ant puts the clear path to storing the knowledge, and used it in developing the performance work in schooling.